Design Thinking, An Examination of Epistemological Frameworks in an Area of Academic Study - Gibbs, William J. (Design and Technology Education: An International Journal, 2022)
The ambiguous identity of the digital media field, the ubiquity of media, and rapid and persistent technological change and innovation pose inimitable challenges for academic programs of study in digital media. Digitization of media is an underlying impetus for today’s rapid innovation that compels related academic programs in higher education to re-examine themselves to keep pace and to better understand their epistemological foundations. At the same time, digital innovation helped spur renewed awareness of design as a human-centered methodology to solve ill-structured, highly complex problems. Design and Design Thinking provide a potential framework to aid in academic program assessment. This paper examines the Design Thinking framework, an iterative process involving students, faculty, and academic and industry partners, to aid in better understanding the philosophical underpinnings of a digital media program and from which to evaluate and design the curriculum.